2017
DOI: 10.1111/ger.12294
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of silver diamine fluoride: Effectiveness and application in older adults

Abstract: This systematic review evaluates the use of SDF for both root caries prevention and arrest in older adults. Existing reports of SDF trials support effectiveness in root caries prevention and arrest, remineralization of deep occlusal lesions and treatment of hypersensitive dentin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 39 publications
(149 reference statements)
1
98
0
Order By: Relevance
“…In the only systematic review of SDF on adults, Hendre and colleagues 53 (2017) found no studies on coronal caries, but included 3 studies on root caries arrest and prevention. They found a preventive fraction for SDF of 24% in a 24-month study and 71% over a 36-month study.…”
Section: Current Evidence On the Efficacy Of Silver Diamine Fluoride mentioning
confidence: 99%
See 1 more Smart Citation
“…In the only systematic review of SDF on adults, Hendre and colleagues 53 (2017) found no studies on coronal caries, but included 3 studies on root caries arrest and prevention. They found a preventive fraction for SDF of 24% in a 24-month study and 71% over a 36-month study.…”
Section: Current Evidence On the Efficacy Of Silver Diamine Fluoride mentioning
confidence: 99%
“…36 SDF seems to be compatible with GIC and its effect on the bond strength of composite to treated dentin is still under study. 53 Laboratory observations report that SDF may also increase resistance of GIC and composite restorations to secondary caries. 63 Long-term clinical studies are required to recommend solid treatment protocols.…”
Section: Current Evidence On the Efficacy Of Silver Diamine Fluoride mentioning
confidence: 99%
“…The use of SDF in the geriatric population has been shown effective in arresting root caries [5,6]. Surgical approaches for managing root caries remain a challenge in this population, and having a chemotherapeutic option that can be delivered in a non-clinical setting has additional advantages.…”
Section: Potential Sdf Benefits To Specific Populations and Patient/pmentioning
confidence: 99%
“…Over the past 100 years, cavitated lesions caused by dental caries have been primarily managed surgically to remove the diseased tissues and replace the lost tooth structure with a variety of dental materials [2]. There have been multiple clinical trials and several systematic reviews indicating application of SDF will arrest or stop progression of caries lesions in a high percentage of cases (30%-70%) [3][4][5][6]. Repeated applications increase the caries lesion arrest rate [6].…”
mentioning
confidence: 99%
“…SDF has likewise demonstrated viability in the administration of root caries in the elderly. It likely has extra appropriateness as an interim approach for overseeing dangerous caries in people currently unable to tolerate more involved dental therapy [29][30][31][32]. Single use of SDF has been accounted for to be lacking for the supported benefit [33].…”
mentioning
confidence: 99%